Comparative Lipidomics and Proteomics of Lipid Droplets in the Mesocarp and Seed Tissues of Chinese Tallow (Triadica sebifera) - Zhi, Yao; Taylor, Matthew C.; Campbell, Peter M.; Warden, Andrew C.; Shrestha, Pushkar; El Tahchy, Anna; Rolland, Vivien; Vanhercke, Thomas; Petrie, James R.; White, Rosemary G.; Chen, Wenli; Singh, Surinder P.; et al. (Frontiers in Plant Science, 2017)
Lipid droplets (LDs) are composed of a monolayer of phospholipids (PLs), surrounding a core of non-polar lipids that consist mostly of triacylglycerols (TAGs) and to a lesser extent diacylglycerols. In this study, lipidome analysis illustrated striking differences in non-polar lipids and PL species between LDs derived from Triadica sebifera seed kernels and mesocarp. In mesocarp LDs, the most abundant species of TAG contained one C18:1 and two C16:0 and fatty acids, while TAGs containing three C18 fatty acids with higher level of unsaturation were dominant in the seed kernel LDs. This reflects the distinct differences in fatty acid composition of mesocarp (palmitate-rich) and seed-derived oil (α-linoleneate-rich) in T. sebifera. Major PLs in seed LDs were found to be rich in polyunsaturated fatty acids, in contrast to those with relatively shorter carbon chain and lower level of unsaturation in mesocarp LDs. The LD proteome analysis in T. sebifera identified 207 proteins from mesocarp, and 54 proteins from seed kernel, which belong to various functional classes including lipid metabolism, transcription and translation, trafficking and transport, cytoskeleton, chaperones, and signal transduction. Oleosin and lipid droplets associated proteins (LDAP) were found to be the predominant proteins associated with LDs in seed and mesocarp tissues, respectively. We also show that LDs appear to be in close proximity to, a number of organelles including the endoplasmic reticulum, mitochondria, peroxisomes and Golgi apparatus. This comparative study between seed and mesocarp LDs may bridge some of the fundamental gaps in knowledge andshed some light on develop an integrated picturethe structure of plant LDs by significantly addressing the limited and improve our understanding of their structure, their functionality and cellular metabolic networks in oleaginous plant tissues.